A study of the microwave amplification in MILO with the flat interaction space - Gorban’, A.M.; Lonin, Yu.F.; Sarukhanyan, G.E. (Вопросы атомной науки и техники, 2018)
The magnetically insulated transmission line oscillator (MILO) is the crossed field device developed for generation of microwave power at gigawatt level. We have used a numerical simulation method to investigate electromagnetic oscillations in MILO where a plane region of interaction between the flow of electrons and the field of the slow-wave structure is installed. The system under study is a segment of the plane transmitting line of an infinite width. The slow-wave structure in the form of a comb is placed on one of the electrodes (anode). The other electrode (cathode) is an explosive electron-emitting source. The line areas on the left and on the right of the slow-wave structure are filled with absorbent to prevent the electromagnetic wave reflection. After the voltage application to the transmission line, an electron flow magnetic self-insulation mode is installed. The slow-wave structure is exited by an external signal. The results obtained for this model were used to calculate the transfer ratio as a function of the exciting signal amplitude and signal frequency detuning with respect to the slow-wave structure principal mode. The spectral characteristics of output signals have been estimated for different excitation modes. The spectral characteristics of output signals have been estimated for different excitation modes.